Foundation Flash CS5 for designers - Green, Thomas J. , 1952-; Dias, Tiago , 1978- (friendsofED : Distributed to the book trade worldwide by Springer Science+Business Media, 2010)
Provides instructions and exercises to help master the fundamentals of Flash CS5, covering such topics as symbols and libraries, ActionScript, audio, text, animation, 3D tools, video, XML, CSs, and Flash movies.